FAMILY FARMERS AND ADAPTATION STRATEGIES IN PANDEMIC COVID-19: study with organic producers based on agroecolgy - Estefano Benedito, Fabiana; Mundo Neto, Martin (Revista Interface Tecnológica, 2022)
The Covid-19 pandemic has had global impacts, affecting all social layers. However, some social groups with higher indicators of vulnerability have suffered more broadly the impacts of the pandemic. The aim of this article was to identify the adaptation strategies adopted by family farmers, organic producers with agroecological practices, during the pandemic. The empirical study was carried out with farmers of the Organization of Social Control - OCS Santa Helena, in São Carlos-SP. The interviews were conducted at the organic street market and during a visit to OCS farmers. Among the economic impacts indicated in the interviews is the decrease in monetary revenue stemming from the interruption of street markets and the suspension of contracts of the Programa Nacional de Alimentação Escolar - PNAE. The main adaptation strategies of this group were i) mobilize the local agroecology network, expanding sales by orders using internet and ii) act with representatives of the municipal political sphere to defend the interests of family farmers.
Keywords: Family farming; Agroecology; Covid-19; Organization of Social Control; Organic Agriculture